An integrated composite with a porous Cf/C-ZrB2-SiC core between two compact outer layers of Cf/C-ZrB2-SiC and Cf/C-SiC. Issue 3 (March 2015) - Hu, Chenglong; Pang, Shengyang; Tang, Sufang; Wang, Yongcai; Cheng, Hui-Ming
Abstract In order to achieve the goals of thermal protection, structure load-bearing and weight reduction of thermal protection materials, a multifunctional integrated composite is fabricated by the combination of slurry infiltration and isothermal chemical vapor infiltration, which has a porous Cf/C-ZrB2-SiC core between two outer layers of compact Cf/C-ZrB2-SiC and Cf/C-SiC. Compared to a Cf/SiC composite with a density of 2.1 g cm−3, the material presents a low density of 1.65 g cm−3 and a 65% lower thermal conductivity in-thickness (3.29 W m−1 K−1), while its flexural strength is 260 MPa, only 16% lower. In addition, the integrated composite exhibits a good ablation resistance with a linear ablation rate of 0.79 μm/s for 1000 s.